Interventions to promote work ability by increasing physical activity among workers with physically strenuous jobs: A scoping review. Issue 2 (March 2021) - Mänttäri, Satu; Oksa, Juha; Lusa, Sirpa; Korkiakangas, Eveliina; Punakallio, Anne; Oksanen, Tuula; Laitinen, Jaana
Aims : The potential benefits of workplace physical activity (PA) interventions are in improving both health and important workplace outcomes. Despite the differences in PA level between physically strenuous and inactive work, the literature reporting the effectiveness of the interventions does not usually differentiate physically active and inactive jobs. The aim of the current study was therefore to collect and synthesise research evidence on workplace PA interventions to promote work ability specifically among workers in physically strenuous jobs by means of a scoping review. Methods : The databases Medline, Cochrane Central and Scopus were used to identify interventions to promote work ability by increasing PA among workers in physically strenuous jobs. An iterative method was used to obtain an overview of the study elements and to extract details on the study design, sample, intervention, outcomes and effectiveness. Results : A total of 47 studies evaluating eight categories of interventions were found. Out of these, 18 reported significant effects on work ability. Positive results came from a range of different interventions, including aerobic exercise, strength training, combined aerobic exercise and strength training, stretching, yoga, consultation and tailored physical exercise programmes. Conclusions : Few interventions were effective in promoting work ability by increasing PA among workers in physically strenuous jobs. In particular, trials based on the demands of work, multimodal interventions and applying wearable technology are needed .